THE PHENOMENOLOGY OF BIPOLAR DISORDER: WHAT DRIVES THE HIGH RATE OF MEDICAL BURDEN AND DETERMINES LONG-TERM PROGNOSIS? - Soreca, Isabella (2009)
Bipolar disorder (BD) has been classically described as one of episodic mood disturbances. New evidence suggests that a chronic course and multisystem involvement is the rule, rather than the exception, and that together with disturbances of circadian rhythms, mood instability, cognitive impairment, a high rate of medical burden is often observed. The current diagnostic approach for BD neither describes the multisystem involvement that the recent literature has highlighted nor points toward potential predictors of long- term outcome. In light of the new evidence that the long-term course of BD is associated with a high prevalence of psychiatric comorbidity and an increased mortality from medical disease, we propose a multidimensional approach that includes several symptom domains, namely affective instability, circadian rhythm dysregulation, and cognitive and executive dysfunction, presenting in various combinations that give shape to each individual presentation, and offers potential indicators of overall long-term prognosis.